Laporan Kasus: Tatalaksana Pneumonia Komunitas di Rumah Sakit Toto Kabila - Papeo, Dizky Ramadani Putri; Putra, Andi El Jalaludin; Gubali, Jihan AR.; Gilalom, Amanda Septiyani; Abd. Latif, Novia Nur Agiska; Idrus Mohamad, Marsela; Ngani, Altaufik (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Pneumonia is an acute respiratory infection affecting the terminal bronchioles and alveoli, commonly caused by bacteria, viruses, or fungi, and remains a leading cause of morbidity and mortality, particularly in extreme age groups. This study aims to describe the clinical presentation, risk factors, and evaluate diagnostic and therapeutic approaches in a patient with community-acquired pneumonia at Toto Kabila General Hospital. A case study was conducted on a 77-year-old male patient presenting with a three-day fever, two-month chronic cough, and epigastric pain. Diagnosis was established through history taking, physical examination, chest X-ray showing bilateral patchy opacities and aortic dilatation, and laboratory tests including hematology, clinical chemistry, and Widal serological test. Treatment included intravenous followed by oral levofloxacin, fluid infusion, antipyretics, N-acetylcysteine and ambroxol, vitamins, and albumin to correct hypoalbuminemia. Data were analyzed descriptively to assess the consistency between clinical findings, diagnosis, and therapeutic response. Laboratory results revealed leukocytosis (12.38×10³/µL), mild hypoalbuminemia (2.4 g/dL), and a positive Widal titer of 1/320, supporting a diagnosis of bilateral pneumonia with secondary typhoid fever. After seven days of treatment, the patient showed improvements in body temperature, respiratory function, and sputum clearance, along with better hemodynamic stability. A multimodal pharmacological and non-pharmacological approach was effective in improving the clinical condition of an elderly pneumonia patient.